Shared Memory Tile-Based vs Hybrid Memory GOP-Based Parallel Algorithms for HEVC Encoder - Migallón, Héctor; López-Granado, Otoniel; Galiano, Vicente; Piñol, Pablo; Malumbres, Manuel P. (Algorithms and Architectures for Parallel Processing, 2016)
After the emergence of the new High Efficiency Video Coding standard, several strategies have been followed in order to take advantage of the parallel features available in it. Many of the parallelization approaches in the literature have been performed in the decoder side, aiming at achieving real-time decoding. However, the most complex part of the HEVC codec is the encoding side. In this paper, we perform a comparative analysis of two parallelization proposals. One of them is based on tiles, employing shared memory architectures and the other one is based on Groups Of Pictures, employing distributed shared memory architectures. The results show that good speed-ups are obtained for the tile-based proposal, especially for high resolution video sequences, but the scalability decreases for low resolution video sequences. The GOP-based proposal outperforms the tile-based proposal when the number of processes increases. This benefit grows up when low resolution video sequences are compressed.